PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA PLASTISIN UNTUK MENINGKATAKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATERI BENTUK MOLEKUL KELAS X SMAN 1 SEKADAU - Yudie Harisandi (Universitas Papua, Manokwari, Indonesia, 2020)
AbstractThe purpose of classroom action research is to solve real problems that occur in the classroom and increase the real activities of teachers in their professional development activities. The classroom action research design used is the Kemmis model, which consists of 4 stages of research, namely planning, implementation, observation, and reflection. The results of data analysis showed that the teacher's activity in implementing discovery learning through animation media on chemical bonding material at SMAN 1 Sekadau increased with a percentage of 88.45% in the first cycle, 92.60% in the second cycle and 96.30% in the third cycle. Student activities in applying discovery learning through animation media on chemical bonding material at SMAN 1 Sekadau have a high percentage value in each activity. The learning outcomes of class X MIA-1 students at SMAN 1 Sekadau, experienced an increase in chemical bonding material after discovery learning was applied through animation media, namely cycle I with classical completeness in cycle I reaching 50%, cycle II 76%, and cycle III 93%. The value obtained is following the KKM standard on chemical bonding materials. Keywords: Classroom Action Research, Plasticine Media, Learning Motivation, Discovery